2015
DOI: 10.1007/s13595-015-0492-7
|View full text |Cite
|
Sign up to set email alerts
|

European beech, silver fir, and Norway spruce differ in establishment, height growth, and mortality rates on coarse woody debris and forest floor—a study from a mixed beech forest in the Western Carpathians

Abstract: Abstract& Key message In mixed forests, coarse woody debris promotes the successful establishment and growth of conifers and beech. In contrast to beech and fir, older spruce seedlings were only present on coarse woody debris and not on the forest floor. & Context Coarse woody debris (CWD) is considered a suitable seedbed for small-seeded and light-demanding species. Its role in enhancing tree regeneration is well reported in boreal or subalpine spruce forests. Less is known about its role in the establishment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…The differences in germinant and seedling counts can be explained by differences in the masting interval between the two sites and by differences in the species share of the mature stands. In 2006 and 2007, we observed many fir germinants in GNP (Orman & Szewczyk ) which boosted the number of fir seedlings in consecutive years. However, we should not underestimate the differences in CWD structure between the plots.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The differences in germinant and seedling counts can be explained by differences in the masting interval between the two sites and by differences in the species share of the mature stands. In 2006 and 2007, we observed many fir germinants in GNP (Orman & Szewczyk ) which boosted the number of fir seedlings in consecutive years. However, we should not underestimate the differences in CWD structure between the plots.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, we observed fewer differences in fir seedling densities growing on different CWD species than in the case of beech and spruce seedlings. Interestingly, a similar study, focused on the same three species in the Western Carpathians, also showed that among all species, fir exhibited minimal substrate preference when comparing CWD with the forest floor (Orman & Szewczyk ). In general, seedling and germinant densities for all species were higher on beech CWD compared with fir and spruce CWD.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations